OEUVRES - Lenin (1974)
CONTENIDO: V. 1 1893-1894. -- V. 2 1895-1897. -- V. 3 LE DEVELOPPEMENT DU CAPITALISME EN RUSSIE. -- V. 4 1898 AVRIL 1901. -- V. 6 JANVIER 1902-AOUT 1903. -- V. 7 SEPTEMBRE 1903- DECEMBRE 1904. -- V. 8 JANVIER-JUILLET 1905. -- V. 9 JUIN-NOVEMBRE 1905. -- V. 10 NOVEMBRE 1905-JUIN 1906. -- V. 11JUIN 1906-JANVIER 1907. -- V. 12 JANVIER-JUIN 1907. -- V. 13 JUIN 1907-AVRIL 1908. -- V. 14 1908. -- V. 15 MARS 1908-AOUT 1909. -- V. 16 SEPTEMBRE 1909-DECEMBRE 1910. -- V. 17 DECEMBRE 1910-AVRIL 1912. -- V. 18 AVRIL 1912-MARS 1913. --V. 19 MARS-DECEMBRE 1913. -- V. 20 DECEMBRE 1913-AOUT 1914. -- V. 21 AOUT 1914-DECEMBRE 1915. -- V. 23 AOUT 1916-MARS1917. -- V. 24 AVRIL-JUIN 1917. -- V. 25 JUIN-SEPTEMBRE 1917. -- V. 26 SEPTEMBRE 1917-FEVRIER 1918. -- V. 28 JUILLET 1918-MARS 1919. -- V. 29 MARS-AOUT 1919. -- V. 30 SEPTEMBRE1919-AVRIL 1920. -- V. 31 AVRIL-DECEMBRE 1920. -- V. 32 DECEMBRE 1920-AOUT 1921. -- V. 34 LETTRES NOVEMBRE 1895-NOVEMBRE 1911. -- V. 35 LETTRES FEVRIER 1912-DECEMBRE 1922. -- V. 36 1900-1923. -- V. 37 LETTRES A SA FAMILLE 1893-1922. --V. 38 CAHIERS PHILOSOPHIQUES. -- V. 39 CAHIERS DE L'IMPERIALISME. -- 41 1896- OCTOBRE 1917. -- V. 42 OCTOBRE 1917-MARS 1923. -- V. 43 DECEMBRE 1893-OCTOBRE 1917. -- V. 44 OCTOBRE 1917 - NOVEMBRE 1920